Geometric Morphometric and Volumetric Analysis of Lumbar Vertebrae For Forensic Anthropology and Clinical Applications: A Mini Review - Maher A M Abumosameh; Aspalilah Alias; Muhammad Faiz Mohd Fauad; Choy Ker Woo; Nadiawati Abdul Razak; Rina Haryani Othman (USIM Press, 2025)
International Conference On Syariah, Law And Science 2024 (CFORSJ i-CONF 2024) 7 November 2024 - 30 November 2024 Editorial Team: Wan Abdul Fattah Wan Ismail, Lukman Abdul Mutalib, Zulfaqar Mamat, Aspalilah Alias, Hasnizam Hashim, Ahmad Syukran Baharuddin, Muhammad Aniq Aiman Alias, Tuan Mohd Faris Hamzi Tuan Ibrahim, Radin Ahmad Taufik Salikin Izzaddin, Ahmad Salman Mohd Yusof. Organized : Centre of Research for Fiqh Forensics and Judiciary (CFORSJ), Faculty of Syariah and Law, USIM